A Problem of Particulate Contamination in an Automated Assembly Machine Successfully Solved by CFD and Simple Experiments - Jatuporn Thongsri (My University, 2017)
Assembly of hard disk drives (HDDs) needs to be done in an automated assembly machine (AAM) virtually free of particulate contamination that can cause them to malfunction. Fan filter units (FFUs) are installed above the AAM to reduce the number of suspended particles in the recirculating air flowing over and around them. At one time, several HDDs were found to be defective. To find out the root cause of this problem, computational fluid dynamics (CFD) was used to investigate the airflow over and around the AAM. It was found that the cause of the high particle counts was improper air speed from the FFUs. The optimal FFUs air speed needed to be in the range of 0.35–0.65 m/s in which the airflow would block out nearby airborne particles and purge away particles generated by the AAM effectively which would, in effect, reduce the particle counts down below the threshold level of class 100 clean room. A few available measurement tools at the factory were then used to perform validating measurements against the simulation results, and the validation was positive. This optimal speed range was implemented at the factory after which the level of contamination was reduced to an acceptable level.
Keywords: Particle (ecology); Factory (object-oriented programming); Aerosol Filtration and Electrostatic Precipitation